2020
DOI: 10.1038/s41416-020-0760-7
|View full text |Cite
|
Sign up to set email alerts
|

Case–control study of paternal occupational exposures and childhood bone tumours and soft-tissue sarcomas in Great Britain, 1962–2010

Abstract: Background This nationwide study investigated associations between paternal occupational exposure and childhood bone tumours and soft- tissue sarcomas. Methods The UK National Registry of Childhood Tumours provided cases of childhood sarcomas born and diagnosed in Great Britain, 1962–2010. Control births, unaffected by childhood cancer, were matched on sex, birth period and birth registration sub-district. Fathers’ occupations were assigned to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…have recently reported higher risks of rhabdomyosarcoma (and marginally higher for total tissue sarcomas) in children of fathers exposed to EEF in the United Kingdom. 39 …”
Section: Discussionmentioning
confidence: 99%
“…have recently reported higher risks of rhabdomyosarcoma (and marginally higher for total tissue sarcomas) in children of fathers exposed to EEF in the United Kingdom. 39 …”
Section: Discussionmentioning
confidence: 99%
“…The risk of RMS was greatest for X-ray exposure in the first trimester, with a 5.7-fold increase (95% CI = 1.2–27.8), and specifically, for the association of X-ray exposure in the first trimester and ERMS (OR = 10.5, 95% CI = 1.5–458.4) [ 34 ]. Additionally, a recent study that examined 1923 RMS cases from the U.K. National Registry of Childhood Tumors found that paternal occupational exposure to electromagnetic fields was associated with RMS risk in the fathers’ children (OR = 1.67, 95% CI = 1.22–2.28) [ 37 ]. However, these associations have yet to be replicated.…”
Section: Non-genetic Risk Factorsmentioning
confidence: 99%
“…Maternal exposure to wood dust was associated with a higher risk of leukemia, and paper and animal dusts were associated with a higher risk of CNS tumors in 2 Danish studies, 6,7 but not in a pooled analysis of international cohorts. 8 Similarly, some studies reported associations between paternal exposure to animal and other organic dusts and leukemias and CNS tumors, [6][7][8][9][10][11] but those results were not replicated by others. 6,8 The small number of exposed cases and the Cancer April 15, 2022 differences in exposure ascertainment methods are some of the factors that might explain the discordance among previous findings.…”
Section: Introductionmentioning
confidence: 99%